TRLS-03. Intracranial activity of tepotinib in patients with MET exon 14 (METex14) skipping NSCLC enrolled in VISION. (9th August 2021) - Bestvina, Christine M; Le, Xiuning; Veillon, Remi; Anderson, Ian; Patel, Jyoti; Demedts, Ingel; Garassino, Marina; Mazières, Julien; Morise, Masahiro; Smit, Egbert; Eggleton, S Peter; O'Brate, Aurora; et al.
Abstract: Background: Brain metastases (BMs) are reported in 20–40% patients with MET ex14 skipping NSCLC. Tepotinib, a highly selective MET inhibitor, has demonstrated an objective response rate (ORR) of 45% and median duration of response (mDOR) of 11.1 months, in MET ex14 skipping NSCLC patients in Cohort A of the Phase II VISION study. Here, we report the intracranial activity of tepotinib in Cohort A. Methods: Patients received oral tepotinib 500 mg QD. Study eligibility allowed for patients with BM (asymptomatic and symptomatic/stable). Primary endpoint: systemic objective response (RECIST v1.1); subgroup analysis in patients with BM (RECIST v1.1) was predefined. An ad hoc retrospective analysis of brain lesions (by CT/MRI) was conducted by an IRC using Response Assessment in Neuro-Oncology Brain Metastases (RANO-BM) criteria. Responses were determined in patients with ≥1 evaluable post-baseline tumor assessment. For non-measurable lesions (enhancing and non-enhancing non-target lesions [NTL]), disease control in the brain was defined as non-complete response/non-progressive disease. Data cut-off: July 1, 2020. Results: Twenty-three patients had baseline BM. Systemic efficacy in patients with BM (ORR 47.8% [95% CI: 26.8, 69.4]; mDOR 9.5 months [95% CI: 5.5, not estimable]) was consistent with the overall population. Fifteen patients were evaluable by RANO-BM; 12 received prior radiotherapy for BM (median 6.4 weeks before treatment). Systemic best objective responses (BORs) were partial response (PR, n=9), stable disease (SD, n=3), and progressive disease (PD; n=3). Of seven patients with measurable CNS disease (all of whom received prior radiotherapy), intracranial BORs were PR (n=5), SD (n=1), and PD (n=1). For patients with NTL only (n=8), one had PD, and seven achieved intracranial disease control with three patients achieving CR of the enhancing NTL. Conclusions: Tepotinib demonstrated intracranial activity in patients with MET ex14 skipping NSCLC with BM. Prospective evaluation of intracranial activity in VISION Cohort C is ongoing.